Study of Genetic Parameters and Yield Potential of Upland Rice Genotypes in Sumatra and Nusa Tenggara Islands - Mustikarini, Eries Dyah; Prayoga, Gigih Ibnu; Faisal, Faisal; Kisman, Kisman; Nusifera, Sosiawan; Saiman, Mohd Zuwairi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
Genotypic performance in rice is significantly influenced by environmental heterogeneity, necessitating multi-location evaluation to identify adaptive and stable upland rice lines. This study evaluates the uniformity, adaptability, stability, and yield potential of five breeding lines (G1–G5) and five released varieties across two contrasting island environments: Jambi (Sumatra) and Mataram (Nusa Tenggara), from June to December 2024. A randomized block design is employed, and data are analyzed using ANOVA, DMRT, correlation analysis, phenotypic and genotypic coefficient of variation, and broad-sense heritability. Significant differences are detected among genotypes for all traits except filled-grain weight, with G2 exhibiting the highest yield per plot. All traits are significantly affected by location, indicating a strong environmental influence, while genotype and environment contributed independently to trait expression. Correlation patterns are generally consistent across locations, with the strongest association observed between yield per plot and grain weight. The majority of traits exhibit broad phenotypic and genotypic variability (87.5%), and 66.7% of the evaluated traits show high heritability, suggesting substantial potential for genetic improvement. Based on performance, lines G2 (white rice) and G5 (red rice) are recommended for further development and cultivation in upland rice ecosystems in Indonesia.